Tinjauan sistematis penggunaan sinbiotik sebagai bahan aditif yang berpengaruh pada produktivitas, status kesehatan, serta kualitas daging ternak unggas - Harvey Febrianta Febrianta; Dave Mangindaan; Bayu Meindrawan (Fakultas Pertanian Universitas Majalengka, 2025)
Synbiotic is a combination of probiotics and prebiotics that provide benefits for improving feed digestibility and the balance of microorganisms in the digestive tract of poultry to support health. In the context of synbiotics, probiotics act as living microorganisms that inhabit the digestive tract, while prebiotics serve as food for these probiotics. This combination aims to enhance the positive effects of live microorganisms and facilitate their proliferation in the intestine. The use of synbiotics in basal feed can reduce feed costs so that farmers get higher profits. Therefore, we conducted a systematic literature review of published studies related to the use of synbiotics in poultry in terms of composition, method of use, and results obtained. There are more than 1200 titles displayed related to nutritional supplements obtained from data extracts on Scopus as a result of searching the database. Subsequently, the screening stage was carried out so that 36 relevant journals were discussed in detail in this systematic review. The results of the mapping and review of the articles showed that synbiotic supplementation has a positive effect on productivity as well as being able to inhibit the growth of pathogenic bacteria and increase the shelf life of poultry meat.